Study of age, sex and body mass index wise variation in C-peptide level among urban population of Northern part of Bihar - Kumar, Rajeev; Priyadarshini, Indu; Goyal, Alka; Swarn, Swarnim; Singh, Sude Kumar (International Journal of Advances in Medicine, 2023)
Background: Different factors regulate the insulin level in blood. Earlier C-peptide was considered as by product of insulin biosynthesis and its role in body seems to be negligible. C-peptide at low physiological concentrations mimics the effects of insulin. However, in the presence of elevated level of insulin concentrations concomitant raised level of C-peptide may blunt peripheral effects of insulin age. This study was carried out to verify the age, sex, and BMI wise variation in level of C-peptide among apparently healthy individual and its contribution in fine-tuning of the tissue’s metabolism under different physiological conditions. Methods: This is a prospective cross-sectional observational study. Estimation of serum c-peptide level was done by solid phase direct sandwich enzyme linked immunosorbent assay (ELISA) kit method. Glucose is estimated by Glucose oxidase peroxidase (GOD-POD) end point colorimetric method and HbA1C was estimated by ion exchange resin method (kit method). Result: Serum C-peptide level is significantly high in advance age and males in compared to younger age and females respectively. The mean level of serum C-peptide is higher in higher body mass index (BMI) group compared to lower, but this difference is statistically insignificant. Conclusions: In normal subjects, the level of C-peptide shows positive correlation with age and BMI. Males have higher level of C-peptide in comparison to females. Apart from these variation C-peptide contributes to different biological effects.